A study on the role of raised serum bilirubin levels in acute appendicitis and its outcomes - Madhavan, Abhilash; Raman, Lakshmana (International Surgery Journal, 2019)
Background: Acute appenidictis is the most common general surgical emergency and early surgical intervention improves outcomes. Despite the increased use of ultrasonography, computed tomography and laparoscopy, the rate of misdiagnosis of appendicitis has remained constant (15.3%) as has the rate of appendicular perforation. Thus, elevated serum bilirubin level will help in the early and accurate diagnosis of acute appendicitis and if so does it have the predictive capacity to warn us about appendicular perforation. Methods: In this study 100 patients were selected as per satisfaction of the inclusion criteria. This study was carried out at SRM medical college hospital between July 2017 to October 2018. All the data findings were recorded and were analysed. Results: In this study 100 patients were selected on satisfying the inclusion criteria. The serum bilirubin levels were recorded for all these patients. Based on the study it was found out that the serum bilirubin levels was elevated in majority of the cases of acute appendicitis and markedly elevated in case of perforated appendicitis. Though the results were not statistically significant the study seems to be clinically significant. Conclusions: Serum bilirubin level seems to be a reliable diagnostic marker for predicting acute appendicitis and perforated or gangrenous appendicitis.